Pengaruh Kompres Hangat terhadap Penurunan Derajat Nyeri Haid pada Remaja Putri di SMA Karya Ibu Palembang - Eka Rahmadhayanti; Rahmalia Afriyani; Annisa Wulandari (Jurnal Kesehatan, 2017)
Painful menstruation or dysmenorrhea was most problem and also be a reason for the decreasing activity of women during menstruation, for example, absent from school. Solving this problem by nonpharmacologic, it is needed to be developed, for example with a warm compress. The aimed of the study was to know the effect of a warm compress to decrease the degree of menstrual pain in teenage girls at senior high school Karya Ibu Palembang 2016. The type of this study was pre-experimental design One group pre and post-test. Samples were obtained based on the inclusion criteria were 18 with accidental sampling technique. The results showed that the average score of the degree of menstrual pain before warm compresses was 2 with a minimum-maximum of 1-3 and after a warm compress was 1 with a minimum-maximum of 1-2. Statistical test result p-value indicates that there was a significant correlation between the degree of warm compresses to decrease menstrual pain (p=0.0001). Suggested for schools can collaborate with health officers in providing counseling to cope with menstrual pain.